FORMS OF PARTICIPATION OF CITIZENS IN PUBLIC ADMINISTRATION - Nemerebayeva, Айгерім Мұхатайқызы (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2020)
The article examines the forms of citizens' participation in public affairs that have arisen in our country in connection with the improvement of the mechanisms of social communication and the development of modern technologies. It was noted that it is effective to distinguish between the forms of citizens' participation in public affairs in three branches of government. Based on the analysis, the article states that improving the forms of citizens' participation in public affairs is an efficient process that has proven its effectiveness. According to the author, the emergence of new forms of citizen participation in public affairs will contribute to greater involvement in the political process in society. This result should be considered as a positive factor influencing the development of the principles of people's power in the Republic of Kazakhstan. With the development of modern information and telecommunication technologies, the state has developed the latest technologies that allow receiving and processing requests from the population through "feedback" channels, as well as promptly reacting to them. The development of means of communication, in particular the development of the Internet, promotes the introduction of new forms of citizen participation in public affairs and the improvement of existing ones. In addition, the author claims that the activity of parties at the local level is one of the guarantees of the realization of the right of citizens to participate in the management of public affairs, since the people elect representatives of the parties.